Efficacy and Safety of Edoxaban in Elderly Patients With Atrial Fibrillation in the ENGAGE AF–TIMI 48 Trial - Kato, Eri Toda (J Am Heart Assoc, 2016)
BACKGROUND: Elderly patients with atrial fibrillation are at higher risk of both ischemic and bleeding events compared to younger patients. In a prespecified analysis from the ENGAGE AF‐TIMI 48 trial, we evaluate clinical outcomes with edoxaban versus warfarin according to age. METHODS AND RESULTS: Twenty‐one thousand one‐hundred and five patients enrolled in the ENGAGE AF‐TIMI 48 trial were stratified into 3 prespecified age groups: <65 (n=5497), 65 to 74 (n=7134), and ≥75 (n=8474) years. Older patients were more likely to be female, with lower body weight and reduced creatinine clearance, leading to higher rates of edoxaban dose reduction (10%, 18%, and 41% for the 3 age groups, P<0.001). Stroke or systemic embolic event (1.1%, 1.8%, and 2.3%) and major bleeding (1.8%, 3.3%, and 4.8%) rates with warfarin increased across age groups (P (trend)<0.001 for both). There were no interactions between age group and randomized treatment in the primary efficacy and safety outcomes. In the elderly (≥75 years), the rates of stroke/systemic embolic event were similar with edoxaban versus warfarin (hazard ratio 0.83 [0.66–1.04]), while major bleeding was significantly reduced with edoxaban (hazard ratio 0.83 [0.70–0.99]). The absolute risk difference in major bleeding (−82 events/10 000 pt‐yrs) and in intracranial hemorrhage (−73 events/10 000 pt‐yrs) both favored edoxaban over warfarin in older patients. CONCLUSIONS: Age has a greater influence on major bleeding than thromboembolic risk in patients with atrial fibrillation. Given the higher rates of bleeding and death with increasing age, treatment of elderly patients with edoxaban provides an even greater absolute reduction in safety events over warfarin, compared to treatment with edoxaban versus warfarin in younger patients. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov/. Unique identifier: NCT00781391.